1982
DOI: 10.1063/1.443603
|View full text |Cite
|
Sign up to set email alerts
|

The electronic structure of CuFeS2, chalcopyrite, from x-ray emission and x-ray photoelectron spectroscopy and Xα calculations

Abstract: The x-ray emission spectra (SKβ, SL, CuKβ, CuL, FeKβ, FeL) and x-ray photoelectron spectra of CuFeS2 chalcopyrite are reported and are interpreted using SCF-Xα MO calculations on the polyhedral anions CuS−74 and FeS−54 and discrete variational Xα band structure calculations. The highest energy occupied orbitals are found to be of Cu3d-S3p antibonding character. Substantial Fe3d character is observed across a broad range of binding energies indicating strong mixing of the Fe3d orbitals with both the Cu3d and S3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…5b that the broader Cu L 3 peak situated $5 eV above the leading absorption peak would arise from transitions to Cu s-states and, to a lesser extent, Cu d-states. Most of the previous electronic structure calculations for chalcopyrite, including those using FEFF8 with the Hedin-Lundqvist exchange potential (Lavrentyev et al, 2004), are in broad agreement with the FEFF8 calculations carried out in the present study (Hamajima et al, 1981;Tossell et al, 1982;Petiau et al, 1988;Kurmaev et al, 1998;Edelbro et al, 2003).…”
Section: Chalcopyritesupporting
confidence: 83%
“…5b that the broader Cu L 3 peak situated $5 eV above the leading absorption peak would arise from transitions to Cu s-states and, to a lesser extent, Cu d-states. Most of the previous electronic structure calculations for chalcopyrite, including those using FEFF8 with the Hedin-Lundqvist exchange potential (Lavrentyev et al, 2004), are in broad agreement with the FEFF8 calculations carried out in the present study (Hamajima et al, 1981;Tossell et al, 1982;Petiau et al, 1988;Kurmaev et al, 1998;Edelbro et al, 2003).…”
Section: Chalcopyritesupporting
confidence: 83%
“…Figure 8 (C2 and C3) shows the effect of Zn substitution on size and morphology in comparison with pure CuInS 2 nanoparticles. [68][69][70][71][72] After substitution, it seems the valence or conduction band relocated respectively due to the p-d hybridization of Fe 3d-Cu 3d states mediated by the anion plike state or 4s state of Fe and Cu to generate a sub-band level (intermediate band) top of the valence band or below the conduction band. Recent studies have been indicated the binary, ternary or quaternary Zn-compounds are sensitive to different synthesis conditions (such as kind of zinc salt, sulfide source or solvent) for controlling of shape.…”
Section: Resultsmentioning
confidence: 99%
“…Recommended calibration values are 931.2 eV for the Cu L 3 peak in CuO and 707.7 eV for the Fe L 3 peak in Fe metal. All theoretical and experimental investigations recognise the covalent character of chalcopyrite which involves extensive overlapping of Cu and Fe metal d orbitals across the whole valence band (Tossell et al, 1982;Kurmaev et al, 1998;Edelbro et al, 2003).…”
Section: Introductionmentioning
confidence: 99%